A classification of live chat service users in the banking industry. Issue 3 (28th February 2019) - Rajaobelina, Lova; Brun, Isabelle; Ricard, Line
Abstract : Purpose: The purpose of this paper is to classify live chat service users in the banking industry and provide relevant descriptive information on each group to be able to suggest appropriate strategies to managers. Design/methodology/approach: A total of 682 panelists from a large Canadian polling firm self-administer a web-based questionnaire. Respondents are users of financial sector live chat services. Two-step cluster analysis was performed. Findings: Four groups emerge from the analysis. Young frequent users (Group 1) attach dominant importance to speed of service, whereas computer users (Group 3) and conservative users (Group 4) who avail themselves of live chat services via computer focus on ease of use. Practical implications: This study, which details four groups of live chat service users in the banking industry, enables managers to better adapt their strategies to the different market segments with a view to providing customers with better quality service and enhancing their experience. Originality/value: The study presents the first live chat service classification to detail user profiles and examine differences at the before, during and after phases of the user experience. Findings enrich the body of academic literature in the service sector, in particular literature focusing on customer service in the banking industry. The paper also provides an interesting managerial framework for the implementation of successful, segment-specific strategies.